PENERAPAN LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN KONSELING REALITAS UNTUK MENGATASI KEBIASAAN PERILAKU AGRESIF SISWA DI SMP NEGERI 2 PA’JUKUKANG - Harceman Harceman; Abdul Saman; Saniasa Saniasa (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
The group’s counselling activities aim to address the behavior habits of aggressive students in SMPN 2 Pa’jukukang. The counsel comes from the initial assessment of student violation records and the results of interviews. Of the assessment results, seven counselors performed aggressive behavior. In group counselling activities carried out using the reality counseling approach using the WDEP procedure with the Paradoxical Prescription technique. The activity is carried out in 3 cycles with the acquisition of assessment results from the counsel on each cycle. On the 1st cycle, the average lift score was 23.14 points in the Good category. On the 2nd cycle, the average lift earned 24.28 points in the Good category. In the third cycle, the average lift score was 29.57 points in the Good category. From the results of these activities, it can be concluded that group counseling services implemented using a reality counselling approach can overcome the aggressive behavior habits of students.